KONSEP PARENTING AL GHAZALI DALAM IHYA ULUMIDDIN - Moh. Najih Surohudin; Adibah Jauhari; Abdul Rouf (FAI- Undar, 2018)
Many people success became a leader, ulama, enterpreneur, and another goodness, but there are many people who success to be a corruptor, impostor, criminaland another vice. They can not achive their success except it made since they have born. Parent are side who most resposibility in this case. Basically, there are no parents who will plunge their children, but it is caused that they doesn’t undersand how to educate their children or maybe their mistake to chose a concept about parenting. Finally they make bad luck to their children. The purpose of this research is to delve a concept abot how to take care of the children (parenting) that proposed by one of moslem education figure Al-Ghazali in this Ihya Ulumiddin book and compare it with concept from another figure. This research is done by review of primary data resources of Ihya Ulumiddin and another secondary data that has related to set of problem. The result of the research shows that there is a seriousness of Al-Ghazali tell about parenting in his book in detail. Many other figures agreed to his concpt. There are only a little people that oppose, especially the concept of modern parenting.